MENINGKATKAN LITERASI PERBANKAN SYARIAH DENGAN MENGEMBANGKAN APLIKASI EDUKASI BERBASIS ANDROID - Khoirul Anam; Lia Anggraini (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2020)
The overall market share of Islamic finance is still below 5% of the total national banking market share. One reason is consumers or the public is still lack of knowledge, understanding and consumer loyalty that is still low on Islamic banks. This research develops an android-based educational application and tests the effectiveness of the application on improving the knowledge of employees of the Baitul Yataama Fadlan Foundation about Islamic banking. Respondents used educational applications and studied Islamic banking content for 2 days. Before and after the respondents used the application, a survey was conducted by asking various questions. The survey aims to see the knowledge of respondents before and after the use of the application, whether there is a significant increase. The results of the first survey using a questionnaire showed results of 47%. Then a second survey was conducted with a result of 67%. There is an increase in the percentage of respondents who answered knowing of Islamic banking by 20%. It can be concluded that the application of Islamic banking education has a significant effect in increasing the knowledge of the respondents.